Prefix And Suffix Analysis In Relation With Students English Ability - Roaini, Roaini; Ansar, Fithrah Auliya (Universitas Islam Negeri Raden Intan Lampung, 2019)
This thesis was about the students’ ability in using prefix and suffix. The purpose of this research was to know how far is the students’ abilities in using prefix and suffix. This research was conducted at the first semester of twelfth grade of SMK BLK Bandar Lampung in 2018/2019 academic year. The type of this research was descriptive quantitative research. The subject of this research was 205 students of twelfth grade in 8 classes. The data of this research was obtained by using test. The researcher analyzed the data by giving score the students’ test, determining the students’ ability classification, and calculating the frequency’s percentage and the average of students’ score, so the students’ ability in using prefix and suffix could be known. Based on the result of the research, the percentage of students’ ability in using prefix and suffix of excellent level students’ score was 3.90% or 8 students, good level students’ score was 17.56% or 36 students, fair level students’ score was 13.17% or 27 students, low level students’ score was 11.22% or 23 students, and failed students’ score was 54.15% or 111 students. The majority of correct prefix was inter- by 172 items, and the majority of correct suffixes were -ment and -ion by 139 items. Moreover, the majority of correct part of speech used in test was verb. In conclusion, the average of students’ ability in using prefix and suffix at the first semester of twelfth grade of SMK BLK Bandar Lampung in 2018/2019 academic year was 46.67. So, it was categorized into low level